2008
DOI: 10.1007/s11104-008-9638-9
|View full text |Cite
|
Sign up to set email alerts
|

Root exudation and rhizosphere acidification by two lines of Medicago ciliaris in response to lime-induced iron deficiency

Abstract: The main objective of this work was to compare the tolerance to lime-induced Fe deficiency of two lines of Medicago ciliaris (TN11.11 and TN8.7). We studied the effects of Fe deficiency on:(1) root biomass and rhizosphere acidification, (2) accumulation in the roots and the exudation into the rhizosphere of organic compounds (citric acid, malic acid and phenols), (3) changes under Fe deficient conditions in the activities of two enzymes, the first related to organic acid metabolism (malate dehydrogenase: MDH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Our results showed that the photosynthetic parameters, leaf Fe content and antioxidant system of the sensitive line TN8.7 were more affected than those of the tolerant TN11.11 line by Fe starvation. These recent findings reinforced our previous work focused in root responses of the same Medicago ciliaris lines [10].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results showed that the photosynthetic parameters, leaf Fe content and antioxidant system of the sensitive line TN8.7 were more affected than those of the tolerant TN11.11 line by Fe starvation. These recent findings reinforced our previous work focused in root responses of the same Medicago ciliaris lines [10].…”
Section: Discussionsupporting
confidence: 91%
“…In previous works [8]- [10], we found that Fe deficiency tolerance in Medicago ciliaris line TN 11.11 is mainly associated with the activation of root plasma membrane H + -ATPase and Fe (III) reductase. In the present study, we investigate some possible mechanisms responsible for Fe deficiency tolerance at leaf level in two Medicago ciliaris lines in order to identify leaf parameters useful for rapid screening of genotypes.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…At the same time, the capacity of the roots to release protons and their H + -ATPase activity were determined by the methods of M'Sehli et al [22] and Shen et al [23], respectively. An in situ visualization technology, as described by Li et al [24] and Yan et al [16], was used to estimate the difference in rhizosphere acidification of both genotypes.…”
Section: Determination and In Situ Visualization Of Fluxed H + And H mentioning
confidence: 99%